2020
DOI: 10.26434/chemrxiv.12899774
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Anthropomorphism: Acting Out General Chemistry Concepts in Social Media Videos Facilitates Student-Centered Learning and Public Engagement

Abstract: <p>This Article describes the educational and public engagement outcomes of an activity called the “ChemClout Challenge” that was implemented in a general chemistry course at UC Riverside. Students worked in groups to make chemistry-themed videos, posted them to social media platforms, then voted on their favorite videos. The majority of students elected to make videos where they anthropomorphized general chemistry concepts, physically acting out principles such as ideal gas law relationships and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…From the students' report, it can be seen that they managed to learn a little about the advanced oxidative process, even if in a little depth, the didactic scientific dissemination video was able to provide this learning to the students. These results are in agreement with the results found in the studies by Hayes et al, 27 Hight, Nguyen, and Su, 28 and Poliakoff, 29 who observed that social media videos were highly effective for audience learning and engagement in chemical concepts.…”
Section: Student 13supporting
confidence: 92%
“…From the students' report, it can be seen that they managed to learn a little about the advanced oxidative process, even if in a little depth, the didactic scientific dissemination video was able to provide this learning to the students. These results are in agreement with the results found in the studies by Hayes et al, 27 Hight, Nguyen, and Su, 28 and Poliakoff, 29 who observed that social media videos were highly effective for audience learning and engagement in chemical concepts.…”
Section: Student 13supporting
confidence: 92%
“…These movies might help students understand laboratories because they have never completed these experiments before. 21,22 We also noticed that the movies provided by the teacher helped to create an engaging laboratory setting. Besides, the students were able to view videos of lab experiments multiple times, each at their own comprehension rate.…”
Section: Video Benefitsmentioning
confidence: 96%
“…Hayes et al (2020) observed that TikTok videos of at-home chemistry experiments can increase knowledge of and interest in chemistry for viewers. In addition to videos showing chemistry experiments, Hight et al (2021) found that students enjoyed creating and consuming content on TikTok that featured anthropomorphized chemistry concepts. Based on an analysis of memetic science content on TikTok, Zeng et al (2020) found that the presence of science on TikTok is dominated by chemistry and physics experiments.…”
Section: Educational Landscape On Tiktokmentioning
confidence: 99%